Analysis of management system and human resource development in improving the profitability of night entertainment businesses at CV. TT Kampung Bule, Batam City - Daniel Daniel; Bambang Satriawan; I Wayan Catrayasa (Journal of Multidisciplinary Academic Business Studies, 2025)
Purpose: This study analyzes how management systems and human resource development practices at Foreplay, a nightlife unit under CV. TT Kampung Bule, affect service quality and profitability. It examines managerial planning, supervision, HR training, and career development, and how these elements relate to customer satisfaction and operational efficiency within the business context. Methodology/approach: A descriptive qualitative approach was used, involving in-depth interviews, direct field observations, and documentation analysis. Participants included the operational manager, Lady Companions (LCs), support staff, and regular customers. Data were processed using thematic analysis supported by source triangulation, member checks, and peer review to ensure validity. Results/findings: Findings show that Foreplay’s management system is unstructured and reactive, with irregular evaluations and incentives unrelated to productivity. HR development is minimal, lacking training, orientation, and career pathways. These weaknesses create inconsistent service quality, low motivation, high turnover, and reduced customer retention. Service quality becomes a crucial intervening factor affecting profitability through customer sensitivity to LC communication, responsiveness, and professionalism. Conclusion: Ineffective management and underdeveloped human resources significantly hinder Foreplay’s profitability despite stable gross income. Strengthening management structure, implementing competency-based HRD, and enhancing service quality are essential to improving long-term performance. Limitations: The study is limited to one nightlife business unit and relies on qualitative perceptions that may not fully capture broader industry patterns. Contribution: This research offers practical managerial insights for nightlife entertainment businesses by emphasizing the strategic role of HR development and structured management systems in improving profitability.